PELAKSANAAN KEWAJIBAN PELAKU USAHA DALAM MENJALANKAN USAHA ANGKUTAN PENYEBRANGAN PASAR KAPUAS-SEBERANG KAPUAS DI KABUPATEN SEKADAU - NIM. A1011201101, PAUL BORNEWIR (Fakultas Hukum Universitas Tanjungpura, 2025)
ABSTRACTThis study discusses about boats or Crossing transportation in Sekadau Regency which still do not meet the standards of supporting facilities such as the lack of seats for passengers, the absence of life jackets, and also do not provide comfort for passengers because some ferry boats are not in a condition that is suitable for use. And do not have official tickets to guarantee insurance for passengers. The problems studied in writing this thesis are